Observational constraints on the origin of the elements: III. Evidence for the dominant role of sub-Chandrasekhar SN Ia in the chemical evolution of Mn and Fe in the Galaxy - Eitner, Philipp; Bergemann, Maria; Hansen, Camilla Juul; Cescutti, Gabriele; Seitenzahl, Ivo; Larsen, Soeren; Plez, Bertrand (Astronomy and astrophysics, 2020)
The abundance ratios of manganese to iron in late-type stars across a wide metallicity range place tight constraints on the astrophysical production sites of Fe-group elements. In this work, we investigate the chemical evolution of Mn in the Milky Way galaxy using high-resolution spectroscopic observations of stars in the Galactic disc and halo stars, as well as a sample of globular clusters. Our analysis shows that local thermodynamic equilibrium (LTE) leads to a strong imbalance in the ionisation equilibrium of Mn I and Mn II lines. Mn I produces systematically (up to 0.6 dex) lower abundances compared to the Mn II lines. Non-local thermodynamic equilibrium (NLTE) radiative transfer satisfies the ionisation equilibrium across the entire metallicity range, -3 < [Fe/H] < -1, leading to consistent abundances from both ionisation stages of the element. We compare the NLTE abundances with Galactic Chemical Evolution models computed using different sources of type Ia and type II supernova (SN Ia and SN II) yields. We find that a good fit to our observations can be obtained by assuming that a significant (~ 75%) fraction of SNe Ia stem from a sub-Chandrasekhar (sub-Ch) channel. While this fraction is larger than that found in earlier studies (~ 50%), we note that we still require ~ 25% near-Ch SNe Ia to obtain solar [Mn/Fe] at [Fe/H] = 0. Our new data also suggest higher SN II Mn yields at low metallicity than typically assumed in the literature.